Perancangan Armatur Lampu Menggunakan Keramik dan Kayu - Cindy Pratignjo; Adi Santosa; Jean Francois Poilot (Intra, 2018)
Interior lamp armature design with ceramic and wood as materials is to consider the mechanism character of both materials. These materials can be collaborated as such to complement in both design and construction system. The pre-eminence of ceramic in general has better pressure quality compared to pull quality, yet the limitation of ceramic is its vulnerability. Related to lamp armature design, ceramic has a character that can reflect lights. Wood which has a character that absorb lights and high durability will be combined to improve the ceramic material character, and relatively low weight and high resistance to chemical and electrical influences. From these collaboration, both mechanical character of the materials compliments each other in designing interior lamp armatures. Armature lamp design also pays attention to market trend, user needs, and theory of literature review. The achieved results are to optimize the mechanical properties of ceramic and wood materials in lamp armature construction system. This design realization helps develop the creativity of local Indonesian craftsmen and becomes a new breakthrough for the interior product design industry.